Determining Effective Dose on Computed Tomography Scan (CT SCAN) in Head Scanning - Firdi Yuana; Kusharto Kusno; Achmad Hidayat (Natural B, Journal of Health and Environmental Sciences, 2011)
Computed Tomography Scan (CT scan) is a diagnostic tool that has very high information. CT scan image is the result of a computer reconstruction of X-ray images. CT scans are widely used to diagnose the disease in and the most commonly used is a CT scan of the head. Impact of CT scan radiation causes direct effects and effects for the patient further. This study aims to determine the effective dose in CT scan of the head at the hospital dr. Scan Soepraoen with Impact software in accordance with the International Commission of Radiological Protection (ICRP). From the results of research conducted on 100 patients showed that the CT Scan Head Dose Length Product (DLP) male patients on average larger of 576 mgy / cm when compared with female patients DLP is 506 mgy / cm. The occurrence of this difference is influenced by the length of the exposure area in male patients on average larger than female patients. There are differences in the calculation of effective dose using ICRP Impact Scan for 103 and ICRP 60. To obtain the value of ICRP 103 1.20 mSv to 1.40 mSv, while for the ICRP 60 values obtained 1.20 mSv. These differences ranged from 0% to 16.7%. This is because the ICRP organ weighting factor 103 larger than the ICRO 60. In addition, the ICRP 60 value Dose Limit (NDB) was not reckoned with the dose derived from medical activity. Difference occur in the calculation of the value of effective dose using ICRP Impact Scan for 103 and ICRP 60. To obtain the value of ICRP 103 1.20 mSv to 1.40 mSv, while for the ICRP 60 values obtained 1.20 mSv. These differences ranged from 0% to 16.7%. This is because the ICRP organ weighting factor 103 greater than the ICRP 60. The results of this study obtained the value of effective dose CT scan of the head in accordance with international standards. This research is also a step synergistic cooperation between the hospitals with UB's Department of Physics.